SASTRA ANAK SEBAGAI MEDIA PENGENALAN NILAI SOSIAL DI MASA PANDEMI (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
Abstract Children's literature is literature that is made by children or adults and is aimed at children. The use of light sentences in children's literature makes it easier for children's literature to be absorbed and accepted by children. In children's literature there are also many social values ​​such as cooperation, love to help, love, like to pray for others, and say the words please and thank you. Children's literature can be used as a medium for the introduction of social values ​​because apart from being easy to convey, children's literature is very interesting to discuss with children. Social values ​​in children's literature can be used as learning and later applied by children in their lives. This article aims to introduce social values ​​through the medium of children's literature.